Determination of estrus duration based on cervical mucus characteristics in Aceh cattle using camera-equipped artificial insemination endoscope - Dian Mulfristia; Hendra Saputra; Cut Nila Thasmi; Hafizuddin Hafizuddin; Ginta Riady; Mudhita Zikkrullah Ritonga; Rosmaidar Rosmaidar (Universitas Airlangga, 2022)
This study aimed to determine the length of the estrus period in Aceh cows based on changes in the characteristics of cervical mucus observed using a camera-equipped artificial insemination (AI) endoscope. This study used twelve healthy and reproductively sound cows aged 4-6 years. All cows were synchronized using prostaglandin F2α (PGF2α) injected intramuscularly twice, 11 days apart. Estrus detection was conducted 24 hours following the second injection of PGF2α three times daily for 30 minutes, respectively. Estrous cows were then subjected to the examination of their cervical mucus at 0, 6, 12, and 18 hours after the beginning of estrus. This study showed that out of 12 samples, only eight cows exhibited estrus signs. Characteristics of cervical mucus of cows at 0 and 6 hours of estrus were transparent. At 12 hours of estrus, five cows showed transparency, and the remaining three cows showed cloudy cervical mucus. Meanwhile, at 18 hours of estrus, all sampled cows showed cloudy cervical mucus then regarded as the end of the estrus. That means the estrus length of Aceh cows in this study was 15.75 ± 3.11 hours. It can be concluded that the determination of the duration of estrus in Aceh cows based on changes in the characteristics of the cervical mucus can be carried out using an AI endoscope with a camera. For further research, it is suggested to apply this estrus detection technique in the implementation of AI and determine the pregnancy rate.